2021
DOI: 10.1038/s41598-021-93938-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial testing the efficacy of a Nurse Home Visiting Program for Pregnant Adolescents

Abstract: To test the efficacy of a nurse home visiting program (HVP) on child development, maternal and environmental outcomes in the first years of life. We conducted a randomized controlled trial to test the efficacy of Primeiros Laços, a nurse HVP for adolescent mothers living in a poor urban area of São Paulo, Brazil. Eighty adolescent mothers were included and randomized to receive either Primeiros Laços (intervention group, n = 40) or healthcare as usual (control group, n = 40). Primeiros Laços is a home visiting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 94 publications
0
11
0
2
Order By: Relevance
“…Another difference between PACT and other early interventions [23][24][25] that have been used in LMICs is the use of video feedback, which promotes and facilitates parental learning of intervention strategies. 11,12,[15][16][17][18][19] If the results of the current trial indicate positive effects of PACT on child development, the use of video-feedback could be considered for incorporation in other early intervention programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another difference between PACT and other early interventions [23][24][25] that have been used in LMICs is the use of video feedback, which promotes and facilitates parental learning of intervention strategies. 11,12,[15][16][17][18][19] If the results of the current trial indicate positive effects of PACT on child development, the use of video-feedback could be considered for incorporation in other early intervention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Large‐scale longitudinal studies have confirmed that impairments in motor, cognitive, and social communication development related to socioeconomic disadvantage, lack of stimulation and learning opportunities and challenging family environments are common among young children in Brazil 20–22 . Despite the global promotion of the importance of early interventions for vulnerable children in these settings, 23,24 few early interventions have been tested for at‐risk young children in Brazil 25 and those programs did not focus on social communication abilities specifically nor use techniques, such as video‐feedback, to enhance the attainment of intervention targets.…”
Section: Introductionmentioning
confidence: 99%
“…In the current report, we conducted analyses on the entire sample (n=80) of adolescent mothers while adjusting for group; the effects of the intervention are reported elsewhere. 51 , 52 The sample’s characteristics are shown in Table 1 . The mean age at baseline was 17.1 years (standard deviation [SD] = 1.2).…”
Section: Methodsmentioning
confidence: 99%
“…Depression symptoms were assessed with the Brazilian Portuguese version of the Beck Depression Inventory, 49 - 51 a 21-item scale that assesses the presence and severity of depression symptoms in the last 2 weeks. Scores range from 0-63, with higher scores indicating more severe depression symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Dentre essas, foi evidenciado uma menor aceleração da idade metilômica no grupo intervenção comparado ao não intervenção e também a metilação do DNA em diferentes regiões mediou a associação entre intervenção e uma resposta cognitiva(Euclydes et al, 2022). Outro estudo revelou um efeito positivo da intervenção no desenvolvimento da expressão de linguagem nas crianças, na responsividade emocional/verbal das mães e oportunidades para variedades na estimulação diária(Fatori D et al 2021). E um outro estudo que avaliou a prole, constatou que crianças com 12 meses do grupo intervenção estavam mais apegadas e envolvidas com suas mães quando comparadas ao grupo controle(Alarcão et al, 2021).Dweep, H et al miRWalk2.0: a comprehensive atlas of microRNA-target interactions, Nature Methods, 12(8): 697-697 (2015).…”
unclassified